2019
DOI: 10.1021/acs.bioconjchem.9b00495
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Protein Corona in Nanoflare-Based Biomolecular Detection and Quantification

Abstract: Selective detection and precise quantification of biomolecules in intracellular settings play a pivotal role in the diagnostics and therapeutics of diseases, including various cancers and infectious epidemics. Because of this clinical relevance, nanoprobes with high sensitivity, wide tunability, and excellent biological stability have become of high demand. In particular, nanoflares based on gold nanoparticles have emerged as an attractive candidate for intracellular detection due to their efficient cellular u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 51 publications
0
11
0
Order By: Relevance
“…Its thickness and structure depends on the medium composition but also on the NPs' physicochemical properties and time of exposure (García-Álvarez et al, 2018;Piella et al, 2017). Wang et al, have shown that a protein corona created by albumin adsorption on AuNPs decreased the detection signal of the LSPR sensor by more than 20% compared to the detection signal observed in a buffer solution containing no protein (H. Wang et al, 2019). Most research on protein corona formed around AuNPs has been performed using biological fluids or cell media with only a very few dealing with this point using food matrices.…”
Section: Protein Adsorption On Aunpsmentioning
confidence: 99%
“…Its thickness and structure depends on the medium composition but also on the NPs' physicochemical properties and time of exposure (García-Álvarez et al, 2018;Piella et al, 2017). Wang et al, have shown that a protein corona created by albumin adsorption on AuNPs decreased the detection signal of the LSPR sensor by more than 20% compared to the detection signal observed in a buffer solution containing no protein (H. Wang et al, 2019). Most research on protein corona formed around AuNPs has been performed using biological fluids or cell media with only a very few dealing with this point using food matrices.…”
Section: Protein Adsorption On Aunpsmentioning
confidence: 99%
“…However, many nanomaterials, when introduced to biological fluids, nonspecifically adsorb biomolecules, resulting in the formation of a protein corona around the structure . The protein corona alters the biological stability, biodistribution, , and targeting efficiency of a nanomaterial, sometimes diminishing its therapeutic potential. Though the surface charge, , size, ,, and shape of a nanomaterial can modulate the composition of the protein corona, its formation is largely unavoidable in biological environments.…”
Section: Introductionmentioning
confidence: 99%
“…Nanoparticles administered into the blood can interact nonspecifically with serum proteins and form a shell of protein, called the protein corona [39][40][41][42][43][44]. Protein corona formation is mainly mediated by coulombic and Van der Waals forces, hydrogen bonding, and hydrophobic interactions [45].…”
Section: Modulating Interactions Between Nps and Proteinsmentioning
confidence: 99%